2012
DOI: 10.2478/v10026-012-0063-8
|View full text |Cite
|
Sign up to set email alerts
|

Potential of granulated modified nanozeolites Y for MTBE removal from aqueous solutions: Kinetic and isotherm studies

Abstract: Adsorption of methyl tert-butyl ether (MTBE) from aqueous solutions by granulated modifi ed nanozeolites Y was investigated. Nanozeolite Y powders were converted into granulated zeolites and subsequently modifi ed with two cationic surfactants (20 mmol/dm 3 ), to be used as adsorbent. Granulated nanozeolites were characterized by BET surface area analysis, elemental analysis and X-ray diffractometer. Hexadecyltrimethylammonium (HDTMA-Cl) modifi ed granulated zeolite had more effective performance than N-cetylp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The results of this study were consistent with studies on the uptake of various pollutants by clinoptilolite. It was found that the equilibrium time for the removal of MTBE using various modified clinoptilolites was 4 h (Ghadiri et al 2012).…”
Section: Investigation Of the Experimental Parametersmentioning
confidence: 99%
“…The results of this study were consistent with studies on the uptake of various pollutants by clinoptilolite. It was found that the equilibrium time for the removal of MTBE using various modified clinoptilolites was 4 h (Ghadiri et al 2012).…”
Section: Investigation Of the Experimental Parametersmentioning
confidence: 99%